Political economy and cycling infrastructure investment - Li Meng (Transportation Research Interdisciplinary Perspectives, 2022)
Cycling has been promoted as a healthy, economical, and environmentally friendly mode of travel; however, its use has been hampered by a lack of safe infrastructure. This study revisits the political economy theorems of Adam Smith, Joseph Stiglitz, and Ronald Coase, to better guide government investment decisions on cycling infrastructure and to illustrate the trade-offs between the investment in cycling and automotive infrastructure. When improving infrastructure, there is no perfect policy, so a clear statement should be made to give the public a better understanding. This paper highlights that every road user should consider the difficulties of all other users on the road. Policy makers should consider cyclists’ difficulties and try to find an investment solution that maximizes both cyclists’ and car drivers’ benefits. Putting cycle paths on the side of roads constrains the value of both bicycles and cars; separate cycling paths should be considered. Political economy theorems include moral, wellbeing, and social costs that can help policy makers make the best investments in cycling infrastructure..